(3TQM GdeYdbGJ GdSHY hGdeVGaJjf GdjgGs - (3dCHi LYaQ CMeO Hf eMeO Hf ESeGYjd GdeQGOi GdeUQjs; (3MSjf Hf CMeO Hf MSjf GdRhRfj, CHh YHO Gddg,J (B486 (3g` s ((3YHO Gddg GdOjf Hf eMeO Hf jhSa Hf Ydi Hf QShd s)
(3ChdgG (B:s
(3GdPi LQi Ydjg CeQ CcKQ Cgd GddZI GdEcKGQ ai JaSjQ ZQjH GdTYQ hEYJbGd dWja eGajg ef GdfMh s
(3BNQgG (B:s
(3ef bUjOI GdMGQK Hf MdRg GdjTcQi bhdg (B: (3ef QaY aYdi EVeGQ eHJOC BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cJH CHjGJ GdbUjOI HGdMeQIs
(3fSNI KGdKg HGdeVGaJjf EdjgG eY GNJdGa ai JQJjHgG HGNJdGa ai HYV GdCdaGXs
(3hgj efbhdg Yf fSNI YdjgG bQGAI HJYR Sfg (B777s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs